Bacillus amyloliquefaciens Rescues Glycyrrhizic Acid Loss Under Drought Stress in Glycyrrhiza uralensis by Activating the Jasmonic Acid Pathway - Yue, Liang; Uwaremwe, Constantine; Tian, Yuan; Liu, Yang; Zhao, Xia; Zhou, Qin; Wang, Yun; Zhang, Yubao; Liu, Bailong; Cui, Zengtuan; Dun, Chengchao; Wang, Ruoyu (Frontiers in Microbiology, 2022)
Drought is a major factor limiting the production of the perennial medicinal plant Glycyrrhiza uralensis Fisch. (Fabaceae) in Northwest China. In this study, 1-year-old potted plants were inoculated with the strain Bacillus amyloliquefaciens FZB42, using a gradient of concentrations (CFU), to test for microbe-induced host tolerance of drought condition treatments in a greenhouse experiment. At the concentration of 108 CFU ml-1, FZB42 had significant growth-promoting effect on G. uralensis: the root biomass was 1.52, 0.84, 0.94, and 0.38 times that under normal watering and mild, moderate, and severe drought stress conditions, respectively. Under moderate drought, the positive impact of FZB42 on G. uralensis growth was most pronounced, with both developing axial and lateral roots strongly associated with IAA (indoleacetic acid) accumulation. An untargeted metabolomic analysis and physiological measurements of mature roots revealed that FZB42 improved the antioxidant system of G. uralensis through the accumulation of proline and sucrose, two osmotic adjustment solutes, and by promoting catalase (CAT) activity under moderate drought stress. Furthermore, significantly higher levels of total ﬂavonoids, liquiritin, and glycyrrhizic acid (GA), the pharmacologically active substances of G. uralensis, were found in the roots of inoculated plants after FZB42 inoculation under all imposed drought conditions. The jasmonic acid (JA) content, which is closely related to plant defense responses and secondary metabolites’ production, was greatly increased in roots after the bacterial inoculations, indicating that FZB42 activated the JA pathway. Taken together, our results demonstrate that inoculation with FZB42 alleviates the losses in production and pharmacological metabolites of G. uralensis caused by drought via the JA pathway’s activation.